Unlocking the market potential of electric vehicles in the Philippines: A statistical and neural network approach to customer willingness to purchase electric vehicles - Cruz, Kevien Palaminiano Cabarrubias-Dela; Tolentino, Lean Karlo Santos (International Journal of Innovative Research and Scientific Studies, 2023)
The research aims to identify the key drivers and barriers to EV adoption, inform policymakers and guide future research in the Philippines. The study used a descriptive survey method with 150 Metro Manila car dealership customers as respondents. The research findings indicate that single-family homeowners are willing to invest in EVs if charging infrastructure is available at home. EV safety, dependability, power, performance, design and availability are crucial for increasing EV adoption. Awareness and incentives were identified as hindrances to adoption. The research suggests that technical fixes and policy tools are needed to promote EV adoption and knowledge sharing is necessary to raise customer awareness. A neural network model was created to determine the willingness to purchase an EV. The findings have implications for policymakers, EV manufacturers and stakeholders interested in understanding barriers to EV adoption. The research highlights the importance of safety, reliability and environmental benefits in joint household purchase decisions. The study identifies economic, technological, policy, infrastructure and social barriers to EV adoption and suggests the need for targeted initiatives and information dissemination to overcome these barriers. The report acknowledges limitations and offers avenues for future research to explore additional factors and variables influencing EV adoption.